IMPROVEMENT OF THE STRUCTURE AND MECHANICAL CHARACTERISTICS OF IRON-CARBON ALLOYS AT DIRECT ALLOYING AND MODIFICATION - A. I. Garost; G. P. Goretskij; V. Vajsova; V. G. Pavlovich (Литьë и металлургия)
The resource-saving method of iron-carbon metals smelting, providing direct alloying of melts by metal elements of oxides is developed.